SAT0223 TUBULO-INTERSTITIAL INFILTRATES IN LUPUS NEPHRITIS. (2nd June 2020) - Pacucci, V. A.; Spinelli, F. R.; Giannakakis, K.; Colafrancesco, S.; Truglia, S.; Ceccarelli, F.; Garufi, C.; Alessandri, C.; Conti, F.
Abstract : Background: Lupus nephritis (LN) occurs in up to 60% of patients affected by Systemic Lupus Erythematosus (SLE). The presence of inflammatory infiltrates in glomeruli and/or in tubulo-interstitium (TI) plays an important role in terms of prognosis (1). Ectopic lymphoid structures (ELSs) are clusters of organized lymphoid infiltrates forming at sites of chronic inflammation in non-lymphoid organs (2). Data on ELSs in kidneys of SLE patients are scant (3-5). Objectives: The aim of the study was to evaluate the tubule-interstitial infiltrates (TI-I) organization and to investigate the presence of ELSs. Methods: Kidney sections of SLE patients undergoing a renal biopsy for diagnostic purpose were studied; LN was diagnosed according to the 2003 International Society of Nephrology / Renal Pathology Society classification criteria. Clinical, laboratory and histological data were collected in a standardized, computerized and electronically filled form, including past medical history. The presence of lymphoid aggregates and ELS in the kidney sections were firstly evaluated by hematoxylin-eosin (HE). By using immunohistochemistry (IHC), we characterized the infiltrates by identification of T cells (CD3), B cells (CD20) and follicular dendritic cells (CD21). Results: By HE we evaluated 53 kidney samples from LN patients (F:M = 51:2, mean age at biopsy ± SD years 35±7.7; mean disease duration at date of biopsy ± SD 8±8.3 years). TI-I were found in 33 kidney specimens. By HE we identified a well-defined infiltrate pattern resembling ELS in 13 renal samples. In these samples, we confirmed the presence of organized infiltrates by IHC, with evidence of segregated T and B cells areas in most of them. In one sample, the CD21 staining was positive confirming the presence of ELS (Figure 1 ). Interestingly, this last patient, who failed ciclophosphamide and mycofenolate, responded to rituximab administration and is now in complete LN remission. Moreover TII was negatively correlated with renal remission after induction therapy (P=0.03) independent of the histological class and the induction treatment. Conclusion: Assessment and management of LN patients are greatly facilitated by information obtained by renal biopsy. In the present study the evaluation by HE of 53 kidney samples from patients with LN showed TI-I in 62% of the specimens and a well-defined infiltrate pattern with GC-like features in 39% of those specimens with TI-I, confirmed in IHC. The presence of TII was associated with a worse outcome in response to therapy. Our preliminary results obtained by IHC suggest that ELS could be considered as a biomarker of renal response to B-cell depleting therapy supporting the importance of TI disease. References: [1]Giannakakis K. & Faraggiana T. Histopathology of Lupus Nephritis. Clinic Rev Allerg Immunol 2011 [2]Bombardieri M et al. Ectopic lymphoid neogenesis in rheumatic autoimmune diseases. Nat Rev Rheumatol 2017 [3]Chang A et al. In situ B cell-mediated immune responses and tubulointerstitial inflammation in human lupus nephritis. J Immunol 2011 [4]Shen Y et al. Association of intrarenal B-cell infiltrates with clinical outcome in lupus nephritis: a study of 192 cases. Clin Dev Immunol 2012 [5]Neusser MA et al. Intrarenal production of B-cell survival factors in human lupus nephritis. Mod Pathol 2011 Disclosure of Interests: viviana antonella pacucci: None declared, Francesca Romana Spinelli Grant/research support from: Pfizer, Speakers bureau: Lilly, BMS, Celgene, Konsantinos Giannakakis: None declared, Serena Colafrancesco: None declared, Simona Truglia: None declared, Fulvia Ceccarelli: None declared, Cristina Garufi: None declared, cristiano alessandri Grant/research support from: Pfizer, Fabrizio Conti Speakers bureau: BMS, Lilly, Abbvie, Pfizer, Sanofi